Survival Rate, Growth and Seedling Quality Index of Baringtonia Asiatica Kurz Stump Due to Length Variation of Stems and Roots - Ady Suryawan; Margaretta Christita; Endro Subiandono (Balai Penerapan Standar Instrumen Lingkungan Hidup dan Kehutanan (BPPLHK)Manado, 2016)
There are 14805.14 ha of North Sulawesi coastal ecosystems that has been damaged. Baringtonia asiatica Kurz (Keben) is one type of coastal plants that can be used to protect coastal areas . Unfortunately, the propagation technique of Keben was not widely studied. This study aims to determine the characters of seedlings produced from the stumps of seed germination. The research used Complete Random Design with nine treatments, consisting of combination betwen three levels of root length (0 cm, 5 cm and 10 cm), and three levels of the stems length (5 cm, 15 cm and 30 cm). Parameters for analysis include percent of success, growth and quality index. The results show that root length and stem length factors significantly affect the height and robustness value. Treatment of root length of 10 cm and 5 cm rods allegedly produces the most excellent quality with the survival rates 93%, height 10.3 cm, diameter 1.08 cm, robustness value 2.03 and index of seed quality 1.35. Based on regulation of land rehabilitation, the height of 10 weeks stump have not qualified yet.